(untitled) (Bangladesh Medical Journal, 2016)
Exclusive breast feeding is essential for the physical and mental development of the child. Post-partum breast problem may produce a obstacle on the way of successful breast feeding. So this study was conducted in ICMH, Matuail to find out common post-partum breast problems. All mothers attending at LMC after delivery with breast problems were included in the study. A total 114 samples were taken. All lactating mothers who gave their consent are to be included in the study and who are not willing to participate in the study were excluded. In our study, age distribution of mother shows, 35.96% of mothers were at the age of < 20 years, 58.77% were between 20-30 years and 5.26% were > 30 yrs of age. Among 114 patients, 91.22% of mothers were house wife and 8.77% were working Mother, timing of initiation of breastfeeding was, 12.28% initiated within 1 hours, 78.28% were within 1-12 hours, 4.38% were within 12-24 hours and exclusive breast feeding was given to 63.15% baby and first pre-lacteal feed was given to 36.84%, among them 71.42%. Common problem was, 46.49% mother suffered from not enough milk followed by, 20.17% for poor attachment, 17.54% suffered from breast engorgement and 7.89% suffered cracked nipple, inverted nipple was in 2.63% flat and sore nipple to 1.75% and nipple infection and breast abscess was present in 0.877% mothers. Among them, 100% mother were counseled about breast feeding, 78.95% mother were taught about proper position and attachment, hot or cold compression given to 35.09%, Oketani breast massage given to 30.7% and others to 13.16%. In our study all mothers were counseled on the benefit of breastfeeding at LMC. Further large long term cohort study should be carried out to see the postpartum breast problem during lactation. Bangladesh Med J. 2015 Sep; 44 (3): 136-139